Neural Underpinnings of Proactive Interference in Working Memory: Evidence From Patients With Unilateral Lesions - Ries, Stephanie K.; Schendel, Krista L.; Herron, Timothy J.; Dronkers, Nina F.; Baldo, Juliana V.; Turken, And U. (Frontiers in Neurology, 2021)
Proactive interference in working memory refers to the fact that memory of past experiences can interfere with the ability to hold new information in working memory. The left inferior frontal gyrus (LIFG) has been proposed to play an important role in resolving proactive interference in working memory. However, the role of white matter pathways and other cortical regions has been less investigated. Here we investigated proactive interference in working memory using the Recent Probes Test (RPT) in 15 stroke patients with unilateral chronic lesions in left (n = 7) or right (n = 2) prefrontal cortex (PFC), or left temporal cortex (n = 6). We examined the impact of lesions in both gray and white matter regions on the size of the proactive interference effect. We found that patients with left PFC lesions performed worse overall, but the proactive interference effect in this patient group was comparable to that of patients with right PFC lesions, temporal lobe lesions, and controls. Interestingly, the size of the interference effect was significantly correlated with the degree of damage in the extreme/external capsule and marginally correlated with the degree of damage in the inferior frontal occipital fasciculus (IFOF). These findings suggests that ventral white matter pathways connecting the LIFG to left posterior regions play a role in resolving proactive interference in working memory. This effect was particularly evident in one patient with a very large interference effect (>3 SDs above controls) who had mostly spared LIFG, but virtually absent ventral white matter pathways (i.e., passing through the extreme/external capsules and IFOF). This case study further supports the idea that the role of the LIFG in resolving interference in working memory is dependent on connectivity with posterior regions via ventral white matter pathways.